2011
DOI: 10.1007/s00394-011-0171-x
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose lithium uptake promotes longevity in humans and metazoans

Abstract: PurposeLithium is a nutritionally essential trace element predominantly contained in vegetables, plant-derived foods, and drinking water. Environmental lithium exposure and concurrent nutritional intake vary considerably in different regions. We here have analyzed the possibility that low-dose lithium exposure may affect mortality in both metazoans and mammals.MethodsBased on a large Japanese observational cohort, we have used weighted regression analysis to identify putative effects of tap water-derived lithi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
106
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(120 citation statements)
references
References 10 publications
12
106
0
2
Order By: Relevance
“…Taken together with another finding that an exposure to a comparably low concentrations of lithium chloride extended the life span of Caenorhabditis Elegans, these findings suggest that long-term low-dose exposure to lithium may exert anti-aging capabilities [14] .…”
Section: Trace Lithium Effect On Agingsupporting
confidence: 57%
See 1 more Smart Citation
“…Taken together with another finding that an exposure to a comparably low concentrations of lithium chloride extended the life span of Caenorhabditis Elegans, these findings suggest that long-term low-dose exposure to lithium may exert anti-aging capabilities [14] .…”
Section: Trace Lithium Effect On Agingsupporting
confidence: 57%
“…Interestingly, an inverse correlation was found between lithium levels in drinking water and not only suicide but also all-cause mortality in 18 neighboring Japanese municipalities with a total of 1206174 individuals [14] . Taken together with another finding that an exposure to a comparably low concentrations of lithium chloride extended the life span of Caenorhabditis Elegans, these findings suggest that long-term low-dose exposure to lithium may exert anti-aging capabilities [14] .…”
Section: Trace Lithium Effect On Agingmentioning
confidence: 99%
“…1 In agreement, humans living in areas with relatively high natural lithium levels in their drinking water display reduced all-cause mortality rates and less harmful behavioral problems, like homicide and suicide. 2,3 Other than the necessity of trace amounts of lithium, the benefits of lithium in the treatment of bipolar disorder have been known for .60 years, and despite large efforts of pharmaceutical companies to develop alternatives, lithium is even today the most effective medication for this disease. 4 However, an important drawback of lithium medication is the development of severe renal side effects (Table 1).…”
mentioning
confidence: 99%
“…It is, however, used as a first-line therapeutic agent to control bipolar disorders. Nutritional studies in mammals have recently indicated lithium's importance to health, leading to a suggestion for it to be classified as an essential trace element; it has even been hypothesized that naturally occurring lithium in drinking water may increase the human lifespan [4].…”
mentioning
confidence: 99%